GATRA DALAM BAHASA INDONESIA - I Nengah Mileh (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
[Title: Phrase in Indonesian Language] Indonesian language has a very important position in the Republic of Indonesia. The first position as the national language (October 28, 1928) and the second position as the state language (Chapter XV, article 36 of the 1945 Constitution). The development and founding of Indonesian language is continuously carried out in various ways. Phrase research as one of the elements in the sentence is a real form in the context of developing and fostering Indonesian language. This study aims to describe phrase in Indonesian which includes the notion of phrase, characteristics of phrase, and syntactic functions occupied by phrase. The theory used in this research is Structural theory developed by Ferdinand de Saussure. His views on language as the object of research can be concluded in the form of dichotomies as follows: (1) diachronic study and synchronic analysis, (2) langue and parole, (3) significant and signified, (4) syntagmatic relationships and paradigmatic relationships. Data was collected by observation / observation method which was assisted by note-taking techniques. Data were analyzed by distribution method and synchronous descriptive method which was assisted by substitution and permutation techniques. The presentation of the results of the analysis was done by informal methods with inductive and deductive techniques.